Advancing air navigation engineering for autonomous and sustainable aviation: navigating technological innovation and regulatory frameworks for sustainable flight - Zhaoxuan Ma Yang; Feng Chao Jung (Vertex, 2021)
Autonomous flying and sustainability are transforming the aviation business. This study examines how technology, policy, and society affect air navigation engineering for autonomous and sustainable aviation. A thorough literature analysis shows how navigation algorithms, sensor systems, and communication networks enable safe and efficient autonomous operations. To address autonomous flight's specific problems, aviation authorities, stakeholders, and researchers must collaborate on regulatory evolution. To gain public trust, safety, privacy, and ethics must be addressed. These observations suggest integrating technical innovation, regulatory frameworks, and public education. Sustainable aviation techniques emphasize aircraft route optimization and emissions reduction. The research highlights the collaborative efforts needed to negotiate the complicated landscape of autonomous and sustainable aviation, resulting in an efficient, safe, and environmentally responsible sector. This study guides industry stakeholders, politicians, and researchers toward reimagined flight operations and aeronautical advancement as the aviation sector navigates autonomy and sustainability